The Basics of Arctic Pedagogy (Global Journal of Human-Social Science, 2015)
The purpose of this article is to describe and define the special features of teaching and learning in the northern areas of Finland, especially in Arctic contexts. The article introduces the essence of Arctic pedagogy by introducing its challenges and goals, possibilities and significance. A model of Arctic pedagogy to be applied in northern education is outlined as a five-level action and teaching tool, which is manifested in learning processes, learning environments, teacherhood, educational leadership, and multi-professionalism. The cornerstones of Arctic pedagogy are adapting, understanding, and analyzing Arctic information in learning processes, student-centered caring teacherhood, wide-ranging networking to support learning, and communalism. The relationship between Arctic information, its implementation through Arctic pedagogy, and the goals of Arctic future skills are discussed.
Keywords: learning; teaching; pedagogy; arctic